Fetal intra‐abdominal bowel dilation in prediction of complex gastroschisis. (8th August 2019) - Andrade, W. S.; Brizot, M. L.; Francisco, R. P. V.; Tannuri, A. C.; Syngelaki, A.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objective: To investigate intra‐abdominal bowel dilation (IABD) in the prediction of complex gastroschisis. Methods: This was a retrospective study of 174 singleton pregnancies with isolated fetal gastroschisis, resulting in live birth and with available ultrasound images from visits at both 20–22 and 30–32 weeks' gestation. IABD was measured as the greatest transverse diameter of the most dilated intra‐abdominal bowel segment, by an operator blinded to postnatal outcome. The distribution of IABD measurements in those with complex and those with simple gastroschisis was determined and the best cut‐off value to predict complex gastroschisis was selected using receiver–operating characteristics (ROC) curves. The area under the ROC curve (AUC), detection rate (DR), false‐positive rate (FPR), positive predictive value (PPV) and negative predictive value (NPV) were determined. Results: The study population included 39 (22.4%) cases of complex and 135 (77.6%) cases of simple gastroschisis. In the prediction of complex gastroschisis, the AUC at 20–22 weeks' gestation was 0.742 (95% CI, 0.628–0.856) and the respective value for 30–32 weeks was 0.820 (95% CI, 0.729–0.910). At the IABD cut‐off of 7 mm at 20–22 weeks, DR, FPR, PPV and NPV for complex gastroschisis were 61.5%, 6.7%, 72.7% and 89.4%, respectively, and at IABD cut‐off of 14 mm at 30–32 weeks, the respective values were 64.9%, 5.9%, 75.0% and 90.7%. Conclusion: Measurement of IABD at 20–22 or at 30–32 weeks' gestation is useful in the prediction of complex gastroschisis. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.